Lower bounds on the orders of subgroups connected with Agrawal conjecture - Popovych, R. (Carpathian Mathematical Publications, 2013)
Explicit lower bounds are obtained on the multiplicative orders of subgroups of a finite field connected with primality proving algorithm.